Effect of polyelectrolytes on the kinetics of ionic reactions: III. Hydrolysis of pyrophosphate in poly-(ethyleneimine) solutions - Fernandez Prini, Roberto; Turyn, D.; Baumgartner, E. (North Holland, 1974)
Fil: Fernandez Prini, Roberto Comisión Nacional de Energía Atómica; Argentina